Brahma-related gene-1 promotes tubular senescence and renal fibrosis through Wnt/β-catenin/autophagy axis. Issue 15 (13th August 2021) - Gong, Wangqiu; Luo, Congwei; Peng, Fenfen; Xiao, Jing; Zeng, Yiqun; Yin, Bohui; Chen, Xiaowen; Li, Shuting; He, Xiaoyang; Liu, Yanxia; Cao, Huihui; Xu, Jiangping; et al.
Abstract: Although accelerated cellular senescence is closely related to the progression of chronic kidney disease (CKD) and renal fibrosis, the underlying mechanisms remain largely unknown. Here, we reported that tubular aberrant expression of Brahma-related gene 1 (BRG1), an enzymatic subunit of the SWItch/Sucrose Non-Fermentable complex, is critically involved in tubular senescence and renal fibrosis. BRG1 was significantly up-regulated in the kidneys, predominantly in tubular epithelial cells, of both CKD patients and unilateral ureteral obstruction (UUO) mice. In vivo, shRNA-mediated knockdown of BRG1 significantly ameliorated renal fibrosis, improved tubular senescence, and inhibited UUO-induced activation of Wnt/β-catenin pathway. In mouse renal tubular epithelial cells (mTECs) and primary renal tubular cells, inhibition of BRG1 diminished transforming growth factor-β1 (TGF-β1)-induced cellular senescence and fibrotic responses. Correspondingly, ectopic expression of BRG1 in mTECs or normal kidneys increased p16 INK4a, p19 ARF, and p21 expression and senescence-associated β-galactosidase (SA-β-gal) activity, indicating accelerated tubular senescence. Additionally, BRG1-mediated pro-fibrotic responses were largely abolished by small interfering RNA (siRNA)-mediated p16 INK4a silencing in vitro or continuous senolytic treatment with ABT-263 in vivo . Moreover, BRG1 activated the Wnt/β-catenin pathway, which further inhibited autophagy. Pharmacologic inhibition of the Wnt/β-catenin pathway (ICG-001) or rapamycin (RAPA)-mediated activation of autophagy effectively blocked BRG1-induced tubular senescence and fibrotic responses, while bafilomycin A1 (Baf A1)-mediated inhibition of autophagy abolished the effects of ICG-001. Further, BRG1 altered the secretome of senescent tubular cells, which promoted proliferation and activation of fibroblasts. Taken together, our results indicate that BRG1 induces tubular senescence by inhibiting autophagy via the Wnt/β-catenin pathway, which ultimately contributes to the development of renal fibrosis.